2020
DOI: 10.3390/su12072819
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Preferences for Wine Attributes: A Best-Worst Scaling Analysis

Abstract: The current paper aims to explore consumers’ preferences for wine attributes related to tradition, sustainability, and innovation. A total of 419 regular wine consumers participated in an online survey that took place in Italy. Consumers’ preferences were assessed through a Best-Worst experiment with 11 wine attributes drawn from the literature. The result shows that the wine attributes, more important for consumers, are mainly related to tradition and sustainability. More specifically, the most important attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 38 publications
(70 reference statements)
2
37
0
6
Order By: Relevance
“…Although not the most important criterion for making a wine purchase, the importance of sustainability, among other extrinsic variables, has been documented. Italian wine consumers ranked sustainable certification third, below geographic origin and grape variety, but higher than the other eight attributes, including vintage and price (Stanco et al, 2020). Sauvignon blanc drinkers indicated their' WTP for wine based on several variables, with WTP for wine with a 95/100 critic's score being the highest (US$12.23 over a bottle with no critic score).…”
Section: Ijwbr 341mentioning
confidence: 97%
“…Although not the most important criterion for making a wine purchase, the importance of sustainability, among other extrinsic variables, has been documented. Italian wine consumers ranked sustainable certification third, below geographic origin and grape variety, but higher than the other eight attributes, including vintage and price (Stanco et al, 2020). Sauvignon blanc drinkers indicated their' WTP for wine based on several variables, with WTP for wine with a 95/100 critic's score being the highest (US$12.23 over a bottle with no critic score).…”
Section: Ijwbr 341mentioning
confidence: 97%
“…The BWS approach is a preference elicitation technique developed by Finn and Louviere [18], in which respondents are invited to choose the best (or most preferred) and the worst (or least preferred) items from a series of choice sets [19]. BWS has been shown to better differentiate amongst objects perceived to be of similar importance over alternative rating and direct ranking methods [14], and is widely used in several disciplines, including agricultural environment [12,14,19], health [20], and marketing [21].…”
Section: Survey Designmentioning
confidence: 99%
“…A number of studies investigated preferences and found that taste is an important preference driver in Australian wine consumers [ 69 ] and that that innovative wine attributes, including alcohol-free wine, were ranked among the least important attributes in a sample of Italian wine consumers [ 70 ]. Alcoholic aroma and flavour contributed as positive preference drivers for the acceptance of non-alcoholic beer in a sample of beer consumers [ 71 ].…”
Section: Resultsmentioning
confidence: 99%